Bacteriological Profile of Diabetic Foot Infection and Its Effect on Limb Salvation - Murshed, Mahbub (Journal of Surgical Sciences, 2020)
Background: Foot ulceration has been reported as the leading cause of hospital admission and amputation in individuals with diabetes. Diabetes-related foot ulcers require multidisciplinary management and care, including debridement, offloading, dressings, management of infection, modified footwear and management of extrinsic factors. Objective: To identify the bacterial pathogens responsible for diabetic foot infections and its effect on limb salvation. Methods: This prospective observational and cross sectional study was conducted among 100 diabetic foot ulceration patients in Mainamati Medical College Hospital, Cumilla between the period of January, 2017 to December, 2018. The patients with diabetic foot ulcer Wagner Grade (2-5) irrespective of age and sex were included in the study. They were thoroughly examined and swab from ulcer base was collected by sterile swab stick and container supplied by the microbiology department. A pre-structured, peer reviewed, interview and observation based data collection sheet was prepared that was used as a research tool. Data regarding clinical, hematological and bacteriological profile were recorded by data collection sheet. Data were entered, managed and analyzed. Results: Diabetic foot was very common in the elderly age group (51-60yrs) 38% and male predominant (78%). Staphylococcus aureus (35%) is the commonest pathogens affecting as the gram positive cocci whereas pseudomonas (23%) is the commonest among the gram negative bacilli. Chloramphenicol, Amikacin, Vancomycin were the most sensitive drugs against gram positive cocci whereas, Cefuroxin, Co-trimoxazole and Gentamycin found the most sensitive drugs against gram negative bacilli. Incision, drainage and dressing (31%) found the commonest treatment modality. The other treatment modalities were debridement, dressing and reconstruction conservative dressing, above and below knee amputation, toe disarticulation etc. Conclusion: Diabetic foot is usually affected by Staphylococcus aureus and streptococcus among the gram positive cocci and pseudomonas whereas Chlamydia and E. coli among the gram negative bacilli. For the limb salvage incision & drainage as well as debridement, excision and reconstruction are the mostly chosen procedure. Journal of Surgical Sciences (2020) Vol. 24 (1) : 21-25